Dermal uptake and percutaneous penetration of ten flame retardants in a human skin ex vivo model. (November 2016) - Frederiksen, Marie; Vorkamp, Katrin; Jensen, Niels Martin; Sørensen, Jens Ahm; Knudsen, Lisbeth E.; Sørensen, Lars S.; Webster, Thomas F.; Nielsen, Jesper B.
Abstract: The dermal uptake and percutaneous penetration of ten organic flame retardants was measured using an ex vivo human skin model. The studied compounds were DBDPE, BTBPE, TBP-DBPE, EH-TBB, BEH-TEBP, α, β and γ-HBCDD as well as syn- and anti-DDC-CO. Little or none of the applied flame retardants was recovered in either type of the receptor fluids used (physiological and worst-case). However, significant fractions were recovered in the skin depot, particularly in the upper skin layers. The primary effect of the worst-case receptor fluid was deeper penetration into the skin. The recovered mass was used to calculate lower- and upper-bound permeability coefficients kp . Despite large structural variation between the studied compounds, a clear, significant decreasing trend of kp was observed with increasing log Kow . The results indicate that the dermis may provide a significant barrier for these highly lipophilic compounds. However, based on our results, dermal uptake should be considered in exposure assessments, though it may proceed in a time-lagged manner compared to less hydrophobic compounds. Graphical abstract: Highlights: Dermal uptake of novel flame retardants were studied in ex vivo skin model. Little or no NFRs were detected in the receptor fluid. Significant deposition in the skin was observed. Time-lagged penetration from skin depot may occur. Uptake decreased with increasing log Kow for these very lipophilic compounds.